Dynamic gastric stability and in vitro lipid digestion of whey-protein-stabilised emulsions: Effect of heat treatment. (15th July 2020) - Ye, Aiqian; Wang, Xin; Lin, Quanquan; Han, Jianzhong; Singh, Harjinder
Highlights: Emulsions were digested in an in vitro dynamic gastric model (HGS) and an intestinal model. WPI-stabilized emulsions flocculated with small flocs at low pH. Heated WPI-stabilized emulsions flocculated with large flocs at low pH. The distinct gastric behaviours of these emulsions affect the lipolysis in the intestine. Abstract: The stability behaviours of whey-protein-stabilised emulsions under gastric conditions and the effects on the lipolysis of the emulsions were investigated using an in vitro dynamic human gastric simulator and a subsequent small intestinal model. Under gastric conditions, heated whey-protein-stabilised emulsions flocculated to a greater extent and with a larger floc size, whereas unheated emulsions were more prone to coalescence. The greater extent of flocculation delayed the delivery of oil droplets to the small intestine, leading to a lower amount of oil in the emptied gastric digesta from the heated emulsion in the early period of digestion. The differences in oil content, droplet size and interfacial composition led to a greater rate and extent of lipolysis in the subsequent intestinal digestion in the heated emulsion than the unheated emulsion. The results suggest that the lipid digestion of whey-protein-stabilised emulsions in the intestinal stage could be manipulated by thermal treatment.